Foodscapes, finance, and faith: Multi-sectoral stakeholder perspectives on the local population health and wellbeing in an urbanizing area in Kenya - Wadende, Pamela; Francis, Oliver; Musuva, Rosemary; Mogo, Ebele; Turner-Moss, Eleanor; Were, Vincent; Obonyo, Charles; Foley, Louise (Frontiers in Public Health, 2022)
Abstract Introduction: Rapid urbanization (growth of cities) can upset local population health and wellbeing including by creating obesogenic environments which increase the burden of Non-Communicable Disease (NCDs). It is important to understand how stakeholders perceive the impact of urbanizing interventions (such as the construction of a new hypermarket) on the health and wellbeing of local populations. Low- and Middle-Income Countries (LMICs) lack reliable infrastructure to mitigate the effects of obesogenic environments, so engaging stakeholders who influence dietary habits is one population-level strategy to reduce the burden of NCDs caused by newly built developments. Methods: We conducted key informant interviews with 36 stakeholders (25 regulatory and 11 local community stakeholders) from Kisumu and Homabay Counties of Western Kenya in June 2019. We collected stakeholders’ perspectives on impacts of a new Mall and supermarket in Kisumu, and existing supermarkets in Homabay on the health and well-being of local populations. Results: Through thematic discourse analysis, we noted that some stakeholders thought supermarkets enabled access to unhealthy food items despite these outlets being also reliable food sources for discerning shoppers. Others linked the changing physical environment to both an increase in pollution and different types of diseases. Stakeholders were unsure if the pricing and convenience of supermarkets would stop local populations from buying from their usual small-scale food vendors. The key finding of this study was that engaging relevant stakeholders as part of population health impact assessments of new developments in cities, is important as it directs focus on health equity and prevention in instances of resource constraints. The findings highlight, also, that community members have a strong awareness of the potential for interventions that would improve the health and wellbeing of local populations.